(untitled) (Journal of Management and Social Sciences, 2021)
The debate on the role of women in governance and development processes has remained salient in scholarly discourse in Africa. The central thrust of the gender question is rooted in giving women greater opportunity to contribute to societal development through increased participation in governance and development processes. The debate interrogates two major fundamental facts about gender question in Africa’s public sphere. The first is the numerical strength of women across the nations in the continent. For example, women were credited with 49.2 % of the 2006 Nigerian population census (NPC, 2006) while women constitute approximately 50 % of African population (ECA, 2016). The second is the widely recognized proven competence of African women which they have demonstrated in various areas of human endeavours. At the heart of the gender debate is the thorny question of gender inequality defined in terms of advantages or opportunities available to boys and men relative to the female gender (Burn, 2019).